KUALITAS PELAYANAN DI MUSEUM KAMBANG PUTIH, TUBAN - Putri, Meita Pradani; Rukminingsih, Nunuk (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
Service Quality in Kambang Putih Museum, Tuban. This research was conducted to know the quality of service in Kambang Putih Museum, Tuban in providing service to the visitor. This research is a qualitative descriptive study. The research focus is based on five dimensions of service quality dimension (SERQUAL) according to Parasuraman that is tangibel, reliability, responsivenees, assurance, and emphaty. The results of this study indicate that the quality of service in Kambang Putih Museum, Tuban has applied tangible, reliability, responsivenees, assurance and emphaty dimension thus the indicators are running well enough. Dimensions of responsivenees, assurance and emphaty have gone very well and are in line with visitor expectations. However, there are several dimensions and indicators that have not run well and not according to the wishes of visitors, including tangible dimensions with facility indicators that make the inconvenience of museum visitors and facilities including incomplete facilities, as well as dimensions of reliability with indicators of officers in the field of education is not in the room so that the officers are there and help provide information about the collection and historic objects, due to the lack of educational personnel at the Museum Kambang Putih, Tuban.Â Keywords: Quality of Service, Public Service, Museum